Sir Hugh Plat’s Promotion of Pasta as a Victual for Seamen - Thick, Malcolm (Petits Propos Culinaires, 2024)
The author is a (British) Inspector of Taxes by profession and an agricultural historian by inclination. The present essay is among the first fruits of a study which he is making of the life and works of Sir Hugh Plat. If there are any other people ’out there’ who share this particular interest, he would be glad to be put in touch with them. His address is: 2 Brookside, Harwell, Oxon OX11 OHG.